Brazilian autoimmune encephalitis network (BrAIN): antibody profile and clinical characteristics from a multicenter study - de Freitas Dias, Bruna; Fieni Toso, Fabio; Slhessarenko Fraife Barreto, Maria Eduarda; de Araújo Gleizer, René; Dellavance, Alessandra; Kowacs, Pedro André; Teive, Helio; Spitz, Mariana; Freire Borges Juliano, Aline; Januzi de Almeida Rocha, Letícia; Braga-Neto, Pedro; Ribeiro Nóbrega, Paulo; et al. (Frontiers in Immunology, 2023)
The frequency of antibodies in autoimmune encephalitis (AIE) may vary in different populations, however, data from developing countries are lacking. To describe the clinical profile of AIE in Brazil, and to evaluate seasonality and predictors of AIE in adult and pediatric patients.We evaluated patients with possible AIE from 17 centers of the Brazilian Autoimmune Encephalitis Network (BrAIN) between 2018 and 2022. CSF and serum were tested with TBAs and CBAs. Data on clinical presentation, complementary investigation, and treatment were compiled. Seasonality and predictors of AIE in adult and pediatric populations were analyzed.Results: Of the 564 patients, 145 (25.7%) were confirmed as seropositive, 69 (12.23%) were seronegative according to Graus, and 58% received immunotherapy. The median delay to diagnosis confirmation was 5.97 ± 10.3 months. No seasonality variation was observed after 55 months of enrolment. The following antibodies were found: anti-NMDAR (n=79, 54%), anti-MOG (n=14, 9%), anti-LGI1(n=12, 8%), anti-GAD (n=11, 7%), anti-GlyR (n=7, 4%), anti-Caspr2 (n=6, 4%), anti-AMPAR (n=4, 2%), anti-GABA-BR (n=4, 2%), anti-GABA-AR (n=2, 1%), anti-IgLON5 (n=1, 1%), and others (n=5, 3%). Predictors of seropositive AIE in the pediatric population (n=42) were decreased level of consciousness (p=0.04), and chorea (p=0.002). Among adults (n=103), predictors of seropositive AIE were movement disorders (p=0.0001), seizures (p=0.0001), autonomic instability (p=0.026), and memory impairment (p=0.001).Most common antibodies in Brazilian patients are anti-NMDAR, followed by anti-MOG and anti-LGI1. Only 26% of the possible AIE patients harbor antibodies, and 12% were seronegative AIE. Patients had a 6-month delay in diagnosis and no seasonality was found.Findings highlight the barriers to treating AIE in developing countries and indicate an opportunity for cost-effect analysis. In this scenario, some clinical manifestations help predict seropositive AIE such as decreased level of consciousness, chorea, and dystonia among children, and movement disorders and memory impairment among adults.